New oscillation criteria for third-order neutral differential equations with continuously distributed delay - Gao, Shaoqin; Chen, Zimeng; Shi, Wenying (Applied mathematics letters, 2018)
In this paper, we establish some new criteria for oscillation and asymptotic behavior of solutions of a certain class of third-order neutral differential equations with continuously distributed delay. We study the case of noncanonical equations subject to various conditions. An example is given to illustrate the main results.